Pengaruh Kombinasi Keunggulan Perusahaan dan Keterbatasan Perusahaan terhadap Investment Opportunity Set dan Nilai Perusahaan - Adawiyah, Robiatul (CV. Satria Jaya, 2024)
The purpose of this study was to determine the effect of the combination of company advantages and company limitations on the investment opportunity set and company value in the Indonesia Stock Exchange 2014-2018. The sampling method used purposive sampling, the sample used was 14 companies. The data analysis technique used in this research is Partial Least Square (PLS) by using the WarpPLS 7.0 software application. The research results show that: 1) the combination of firm advantage has a significant positive effect on the investment opportunity set. 2) Company limitations have a significant negative effect on the investment opportunity set. 3) the combination of company advantages has a significant positive effect on firm value. 4) company limitations have a significant negative effect on firm value. 5) The investment opportunity set has a significant positive effect on firm value